芒硝의 瀉下作用이 MCAO 흰쥐 뇌조직의 Bax 및 HSP72 발현에 미치는 영향 - 김건식(Kon Sik Kim); 김범회(Bum Hoi Kim); 이동은(Dong Eun Lee); 양기영(Kee Young Yang); 김성준(Seong Joon Kim); 강희(Hee Kang); 손낙원(Nak Won Sohn) (동의생리병리학회지, 2009)
This study aimed to evaluate the effect of purgation therapy with Natrii sulfas, a therapy for stroke patients with constipation in the oriental medicine, on the ischemic brain damage of the rats. The ischemic brain damage was induced by the middle cerebral artery occlusion (MCAO), Natrii sulafas was administered once after the MCAO. After 48 hours, expressions of Bax, Bcl-2, c-Fos, and HSP72 on the brain tissues were observed by immunohistochemistrical methods or technique. Purgation therapy with Natrii sulfas attenuated the excess of Bax expression caused by the ischemic brain damage. It was significant statistically in the penumbra of cerebral cortex, but not in the caudate putamen, of the MCAO rats. Purgation therapy with Natrii sulfas did not attenuate the excess of Bcl-2 expression caused by the ischemic brain damage. Purgation therapy with Natrii sulfas did not attenuate the excess of c-Fos expression caused by the ischemic brain damage. Purgation therapy with Natrii sulfas attenuated the excess of HSP72 expression caused by the ischemic brain damage. It was significant statistically in the penumbra of cerebral cortex, but not in the caudate putamen, of the MCAO rats. These results suggest that purgation therapy with Natrii sulfas has a neuroprotective effect on the ischemic brain damage and an anti-apoptotic effect. KCI Citation Count: 0